Home tele-rehabilitation for rheumatic patients: impact and satisfaction of care analysis. (February 2017) - Pani, D; Piga, M; Barabino, G; Crabolu, M; Uras, S; Mathieu, A; Raffo, L
Introduction: In this paper, we evaluated patients' perspectives on the use of a system for home tele-rehabilitation, designed for subjects with low computer literacy suffering hand impairment due to rheumatic diseases. Methods: After a clinical trial assessing device effectiveness, the Psychosocial Impact of Assistive Devices Scale (PIADS), Quebec User Evaluation of Satisfaction with Assistive Technology (QUEST) and Individually Prioritised Problem Assessment (IPPA) questionnaires were administered to evaluate the system's impact on each patient's life, and the results were correlated with clinical indices. Patients were asked to continue self-administered rehabilitation with common objects. One year later, a semi-structured telephone interview gathered data on their experience. Results: The system received a positive QUEST score (4.5 ± 0.3) and a modest PIADS score (0.84 ± 0.8) due to the small impact on adaptability and self-esteem. The IPPA (3.7 ± 3.4) revealed improvement in the ability to perform tasks considered important, which was significantly correlated ( r = 0.60; p < 0.02) with the clinical Health Assessment Questionnaire (HAQ) index improvement. The interviews revealed a positive engagement effect, enhanced by the need to develop skills to be able to use the device (technological challenge) and by the perception of more attention by the medical staff. This may explain the significant dropout rate (80%) from the post-trial rehabilitation of the patients who used the device. Discussion: The system was largely accepted by the patients. The results suggest that the need for information on their rehabilitation progress and the technological challenge deserves further study to make patients more autonomous in cases of continuous rehabilitation.